2013
DOI: 10.2298/abs1302549a
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and partial characterization of endoglucanase produced by Streptomyces sp. B-PNG23

Abstract: Streptomyces sp. B-PNG23 was selected as a promising cellulolytic strain and tested for its ability to produce cellulases from agroindustrial residues. A pH value of 7 and temperature of 28°C were found to be optimal for maximum enzyme production. The highest endoglucanase activity was obtained in a medium comprised of wheat bran (2 g/l), yeast extract (2 g/l), NaCl (2 g/l), NH4Cl (2.5 g/l), and (0.4 g/l) of MgSO4. The enzyme was active at a broad range of pH (5-8) and temperatures (40-70°C). The optimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 30 publications
4
8
0
Order By: Relevance
“…NTU-05 (Wanga et al 2009) and Streptomyces sp. B-PNG23 (Azzeddine et al 2013) and similar to that observed for Bacillus subtilis LFS3 (Rawat and Tewari 2012) and Gracilibacillus sp. SK1 (Yu and Li 2015).…”
Section: Characterization Of Purified Endoglucanasesupporting
confidence: 84%
“…NTU-05 (Wanga et al 2009) and Streptomyces sp. B-PNG23 (Azzeddine et al 2013) and similar to that observed for Bacillus subtilis LFS3 (Rawat and Tewari 2012) and Gracilibacillus sp. SK1 (Yu and Li 2015).…”
Section: Characterization Of Purified Endoglucanasesupporting
confidence: 84%
“…In support of these results the highest cellulase activity of Streptomyces sp. B-PNG23 was observed at 28 °C (Azzeddine et al 2013).…”
Section: Optimization Of Culture Conditions For Production Of Cellulasementioning
confidence: 97%
“…The optimum temperature of the A. geliboluensis endoglucanase was higher than some other endoglucanases obtained from Streptomyces sp. B-PNG23 (Bettache et al 2013), Bacillus subtilis (Asha and Sakthivel 2014), and Bacillus mycoides S122C (Balasubramanian et al 2012). Some researchers have also recently reported that endoglucanases showed maximum activity at 60 °C and above 60 °C (Saratale et al 2012;Dipasquale et al 2014).…”
Section: Characterization Of Endoxylanase and Endoglucanasementioning
confidence: 97%
“…B-PNG23 (Bettache et al 2013) secreted high amounts of enzyme when the yeast extract was used in the medium. The suitable incubation temperature for endoxylanase and endoglucanase production from A. geliboluensis was determined.…”
Section: Optimization Of Endoglucanase and Endoxylanase Productionmentioning
confidence: 99%